Kualitas kondisi fisik dan teknik dasar sepak takraw - Purwanto, Didik (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2022)
Monitoring the preparations in the sparring test shows the physical condition of athletes and basic techniques that have decreased. This is necessary to know the quality of physical conditions and basic techniques owned by the Sangkuriang Club sepak takraw team to prepare for participating in the 2022 national competition. This study aims to find out about the quality of physical conditions and basic techniques possessed by Sangkuriang sepak takraw club athletes so that they are used as a basis for evaluating the coaching team in determining team preparation. The research uses quantitative descriptive research methods that use a research approach in the form of test surveys, physical shaving conditions, and basic techniques. The instruments used for the physical condition are the dominant test items in sepak takraw athletes, while the basic techniques of test items are in the form of basic techniques in sepak takraw. The sample in this study was 12 male athletes from the Sangkuriang club. Physical condition; the most numerous category is the good category of 5 people (41.67%). In basic engineering, the most numerous category is moderate five people (41.67%). In the future, it is necessary to know the physical qualities and basic techniques of sepak takraw athletes, aiming that coaches can understand their athletes' abilities.